2015
DOI: 10.1016/j.jnucmat.2015.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Sputtering of mixed materials of beryllium and tungsten by hydrogen and helium

Abstract: The interaction of mixed Beryllium/Tungsten targets with Hydrogen and Helium is studied using the binary collision code SDTrim-SP [1]. We restrict the study to a sub-set of material mixes expected to be stable [2] Be, Be 2 W , Be 12 W , Be 24 W , and W . The dynamic changes of the surface and subsequent effects on sputter rates and other quantities are analyzed. In the mixed systems it is very important to use the dynamic mode, because the change of surface composition by the impact of the projectiles changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Many theoretical studies have focused on this finding [2,10,11,[13][14][15][16][17][18]. By using molecular dynamics simulation, Lasa et al [10] studied the irradiation of Be on W surface at different impacting energies (10-200 eV) and angles (0-75°), and showed that no crystalline alloy structure formed in the W-Be mixed layers after annealing.…”
Section: Introductionmentioning
confidence: 99%
“…Many theoretical studies have focused on this finding [2,10,11,[13][14][15][16][17][18]. By using molecular dynamics simulation, Lasa et al [10] studied the irradiation of Be on W surface at different impacting energies (10-200 eV) and angles (0-75°), and showed that no crystalline alloy structure formed in the W-Be mixed layers after annealing.…”
Section: Introductionmentioning
confidence: 99%
“…Previous DIII-D experimental and modeling results reveal that there exists a large amount of deposited carbon on the surface of tungsten samples, and the existence of carbon has a noteworthy influence on the tungsten erosion process for both inter-and intra-ELM phases [4,7]. Dynamic simulations for the ITER tungsten divertor also show that the deposited beryllium on the tungsten surface significantly affects the total tungsten erosion rate [18]. However, the complicated mixed-material condition in EAST leads to a challenge for modeling of tungsten divertor erosion.…”
Section: Introductionmentioning
confidence: 94%
“…tungsten fuzz [116]), or heterogeneous materials [117] require specialized codes. SDTrimSP-2D [118] is a MC code with BCA allowing calculating the evolution of two-dimensional targets by implant ation and sputtering [115]. CORTEO [104] allows calculating IBA spectra from arbitrary two-dimensional or threedimensional material distributions [119]; STRUCTNRA [120] calculates IBA spectra from arbitrary two-dimensional distributions.…”
Section: Codes For Two-and Three-dimensional Samplesmentioning
confidence: 99%